Small-Scale Artisanal Mining Access Rights: Framing the Welfare State in Realising Social Justice - Rohman, Arif; Syafruddin, Syafruddin; Zein, Yahya Ahmad; Silviana, Arina (Faculty of Law, Universitas Pekalongan, 2024)
Natural resources are utilized for the development and community welfare. Economic potential, however, is made easy by the community so that illegal mining occurs, even though the government accommodates access rights for the community. The purpose of this article is to analyze the existence of rights for the community to access minerals and coal mining. The approach used is a doctrinal approach. The research results: first, limitations and permit procedures become obstacles to individual access. Secondly, post-mining environmental restoration is imposed on local governments so that it becomes a tug of war in considering economic potential and post-mining obligations, which ultimately hinders the fulfillment of community access rights. As a welfare state, government policies related to this matter should consider allocating community mining areas with potential mineral content and preparing human resources through training to create security for the community and awareness of environmental damage.